Computational Fluid Dynamics 2000 : Proceedings of the First International Conference on Computational Fluid Dynamics, ICCFD, Kyoto, Japan, 10-14 July 2000 - Satofuka, N. (Nobuyuki) (Springer Berlin Heidelberg, 2001)
The International Conference on Computational Fluid Dynamics (ICCFD) is the merger of the International Conference on Numerical Methods in Fluid Dynamics (ICNMFD) and the International Symposium on Computational Fluid Dynamics (ISCFD). It is held every two years and brings together physicists, mathematicians and engineers to review and share recent advances in mathematical and computational techniques for modeling fluid dynamics. The proceedings contain a selection of refereed contributions and are meant to serve as a source of reference for all those interested in the state of the art in computational fluid dynamics.